Effect of ocular hypertension on the levels oflipid peroxidation products in anterior eye tissues in experimental diabetes - V.R. Yurevych (Ukrainian Society of Ophthalmologists, 2015)
Background: Even though there has been significant advance in the care of ocular complications of diabetes mellitus, the issue related to the prevention of and therapy for this pathology is still an important area that needs to be addressed. Purpose: To investigate the effect of ocular hypertension on the levels oflipid peroxidation products in anterior eye tissues in experimental diabetes. Materials and Methods: Thirty-two rabbits were divided into four groups: group 1 (controls; 10 rabbits), group 2 (diabetes and ocular hypertension (D+OH) group; 8 rabbits), group 3 (diabetes-only group; 7 rabbits) and group 4 (ocular hypertension-only group; 7 rabbits). In these animals, the levels of malondialdehyde and diene conjugate in the anterior chamber angle tissue and aqueous humor were determined. Results: The activation of lipid peroxidation was seen as increased diene conjugate and malondialdehyde levels in the anterior chamber angle tissue and aqueous humor in animals with diabetes. In D+OH group, the levels of malondialdehyde and diene conjugates in the anterior chamber angle tissue, and the levels of malondialdehyde and diene conjugates in the aqueous humor were 23.8%, 21.1%, 31.9% and 28.1%, respectively, higher than those in diabetic animals without ocular hypertension. Conclusion: Increased lipid peroxidation imbalance found in anterior eye tissues and aqueous humor in animals with diabetes mellitus and experimental ocular hypertension is a key element of the mechanism of the accelerated destruction in the aqueous humor outflow pathways.